Correlation between Categories in the Cognitive and Affective Domain: Korelasi di antara Kategori-Kategori dalam Domain Kognitif dan Afektif - Dwi Ariefin (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2022)
The Cognitive Domain has a categorization from remembering to creating, while the Affective domain from receiving to characterization. Clarity of correlations within and between domains is very necessary for setting learning objectives. This study aims to produce a description that clarifies the correlations within and between domains. This descriptive qualitative research examines information in relevant books and journal articles. Findings were also compared and synthesized with field findings. There are three kinds of correlation. In the LOTS group Cognitive domain learning category and in all Affective domain categories there is a prerequisite graded correlation. Meanwhile, in the HOTS category for the Cognitive domain, there is a multi-order correlation. Two-way support correlations occur in categories in the Cognitive domain with categories in the Affective domain. Categories with higher complexity will include lower levels of complexity. The descriptive findings are useful for the preparation of learning objectives.